Sales Contract: Traditional Doctrine and Issues of Ukrainian Civil Law - Вавженчук, Сергій Ярославович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article analyzes a series of aspects of legal regulation and identifies individual issues regarding thesales contract. Therewith, it identifies peculiarities and elements of the sales contract, pays attention to itsdifficult legal nature.